The Effect of Earnings Management, Multinationality, Internal Control, and Good Corporate Governance on Tax Aggressiveness - Suhirman Madjid; Mazaya Karamina Kusumah (Pusat Riset dan Inovasi Nasional, 2026)
This study examines how earnings management, multinationality, internal control, and good corporate governance affect tax aggressiveness in Indonesian consumer goods companies. Using a quantitative method with purposive sampling, data were analyzed through multiple linear regression. Results show that earnings management and multinationality do not impact tax aggressiveness, while internal control and good corporate governance do. These findings highlight the importance of strong control systems and governance in limiting aggressive tax practices. The study also provides insights for future research to explore other variables and industries.